THE CONTRASTIVE ANALYSIS OF THE ENGLISH – ING CLAUSE AS DIRECT OBJECT AND ITS ALBANIAN CORRESPONDENTS - Aliti, Afrim; Iseni, Arburim (European Scientific Journal, ESJ, 2014)
This paper is a corpus-based contrastive analysis between English and Albanian. It aims at describing and analysing the structural differences and similarities between the nominal functions of the –ING clauses in English and their Albanian correspondents. The data collected in our corpus from fictional sources is contrasted in terms of their syntactic structures. In developing this research towards satisfactory outcomes, the study also includes an error survey of 27 Albanian students from the English Department of the Faculty of Languages, Cultures and Communication at South East European University in Tetova, and 21 students of the fourth year in secondary school at ‗Sami Frashëri‘ in Kumanova. Furthermore, the findings and results of the survey are presented in the table labelled 1.